INFLUENCE OF STAFF DEVELOPMENT PROGRAMMES ON JOB PERFORMANCE OF OFFICE TECHNOLOGY AND MANAGEMENT LECTURERS IN POLYTECHNICS IN NORTHWEST, NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The study investigates the influence of staff development programmes on job performance ofOffice Technology and Management (OTM) lecturers in polytechnics in Northwest, Nigeria.Two research questions guided the study, while two hypotheses were tested. Descriptive surveyresearch design was used for the study. The population of the study was 177 OTM lecturersfrom public polytechnics in North West, Nigeria. The entire population was used. A structured4-point sealed questionnaire containing 20 items in two clusters was used for data collection.Data were analyzed using mean and standard deviation to answer the research questions, whilet-test was used in testing the hypotheses at 0.05 level of significance. Findings revealed thatOTM lecturers in polytechnics in North-West Nigeria agreed that staff development programmesinfluenced their job performance. It was, therefore, recommended among others that, TertiaryEducation Trust Fund (Tetfund), in collaboration with other educational stakeholders shouldmake staff development programmes more accessible to OTM lecturers which will help them toimprove their instructional planning.
Keywords: Influence, Staff development, OTM, Lecturers, Polytechnic